2018
DOI: 10.1097/md.0000000000013335
|View full text |Cite
|
Sign up to set email alerts
|

The time course of cervical alignment after cervical expansive laminoplasty

Abstract: Retrospective Cohort study To analyze cervical lordosis angle (CLA) change after cervical expansive laminoplasty (CEL) over time, and to determine optimal cut-off angle for predicting postoperative kyphosis Postoperative development of sagittal malalignment after laminoplasty is associated with neurological dysfunction and neck pain. However, there is no information on the serial CLA change over time and cut-off angle for predicting postoperative kyphosis The Cobb angle between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…First, our follow-up period was 2 years, which was relatively short. Since it has been reported that most alignment changes after laminoplasty occur within the first 6 months postoperatively, and many cases do not worsen 1 year postoperatively, 27 the evaluation performed 2 years postoperatively in the present study can be considered reasonable. However, reoperation after laminoplasty in OPLL is associated with increased ossification and kyphosis 14 and may have a greater impact on QOL in the long term.…”
Section: Discussionmentioning
confidence: 81%
“…First, our follow-up period was 2 years, which was relatively short. Since it has been reported that most alignment changes after laminoplasty occur within the first 6 months postoperatively, and many cases do not worsen 1 year postoperatively, 27 the evaluation performed 2 years postoperatively in the present study can be considered reasonable. However, reoperation after laminoplasty in OPLL is associated with increased ossification and kyphosis 14 and may have a greater impact on QOL in the long term.…”
Section: Discussionmentioning
confidence: 81%
“…29 Another retrospective cohort study found that the risk of cervical kyphosis after laminoplasty is high when the preoperative CLA is <8.2°. 30 Nevertheless, several investigations have found that preoperative CLA did not correlate with postlaminoplasty loss of cervical lordosis. 17 Similar to the above results, we found that preoperative CLA is not significantly associated with postoperative cervical kyphosis and does not predict postoperative cervical kyphosis.…”
Section: Discussionmentioning
confidence: 98%
“…A prospective cohort study reported that a 7.0° cutoff for preoperative C2–C7 lordotic angle predicts postlaminoplasty kyphosis in patients without preoperative kyphotic alignment 29 . Another retrospective cohort study found that the risk of cervical kyphosis after laminoplasty is high when the preoperative CLA is <8.2° 30 . Nevertheless, several investigations have found that preoperative CLA did not correlate with postlaminoplasty loss of cervical lordosis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, the follow-up period was 1 year. Choi et al [ 33 ] reported that changes in cervical sagittal alignment generally reach a plateau at 6 months after CLP. Thus, the follow-up period was enough to investigate the risks for LCL after CLP.…”
Section: Discussionmentioning
confidence: 99%